Environmental system modeling and landscape management - Nóbrega, Rodrigo Affonso de Albuquerque; Teixeira, Fernanda Zimmermann; Sayago, Doris Aleida Villamizar (Sustainability in Debate, 2020)
Environmental system modeling and landscape management